Analisis Reflektif Kandungan Nilai Pancasila dalam Seni Gamelan Sunda Laras Salendro (Studi Fenomenologi di Program Studi Karawitan Institut Seni Budaya Indonesia Bandung), - Tarsidi, Deni Zein (2017)
Penelitian ini didasarkan pada lima rumusan masalah, yaitu 1) Bagaimana refleksi nilai sila ketuhanan yang maha esa dalam seni Gamelan Sunda laras salendro, 2) Bagaimana refleksi nilai sila kemanusiaan yang adil dan beradab dalam seni Gamelan Sunda laras salendro, 3) Bagaimana refleksi nilai persatuan Indonesia dalam seni Gamelan Sunda laras salendro, 4) Bagaimana refleksi nilai sila kerakyatan yang dipimpin oleh hikmat kebijaksanaan dalam permusyawaratan/perwakilan dalam seni Gamelan Sunda laras Salendro, 5) Bagaimana refleksi nilai keadilan sosial bagi seluruh rakyat Indonesia dalam seni Gamelan Sunda laras salendro. Penelitian ini menggunakan metode fenomenologi, dengan teknik pengumpulan data melalui observasi, wawancara dan analisis dokumentasi. Penelitian ini mengungkapkan bahwa: 1) Refleksi nilai sila ke-1 terdapat dalam mitos goong, ritual dan lirik lagu. 2) Refleksi nilai sila ke-2 terdapat dalam semiotika persamaan gender dalam instrument musik gamelan, cara duduk pemain Gamelan, cara memperlakukan Gamelan dan dalam lirik lagu. 3) Refleksi nilai sila ke-3 terdapat dalam sistem nada yang kontrapung, kebersamaan antar pemain Gamelan dan dalam lirik lagu. 4) Refleksi nilai sila ke-4 terdapat dalam semitika pemimpin dalam instrument musik gamelan. 5) Refleksi nilai sila ke-5 terdapat dalam semua instrumen musik Gamelan, lirik lagu dan rasa yang ditimbulkan setelah menonton pertunjukkan seni Gamelan sunda, Kata Kunci: Reflektif, Nilai, Pancasila, Seni, Gamelan, Sunda, laras Salendro, The study was based on a five-formulation of the problem, namely 1 How is the reflection of the omnipotent divine values in the Sundanese gamelan art of the salendro barrel, 2) How to reflect the values of the just and civilized humanity principle in Sundanese gamelan art of salendro barrel, 3) How to reflect the value of Indonesian unity in Sundanese gamelan art of salendro barrel, 4) How is the reflection of the values of the populist precepts led by the wisdom of wisdom in the deliberations / representations in the art of Sundanese Gamelan Barrel Salendro, 5) How to reflect the value of social justice for all Indonesian people in the art of the Sundanese salon gamelan barrel. This research uses phenomenology method, with data collection technique through observation, interview and documentation analysis. This research reveals that: 1) Reflection of the 1st grade is in the myth of goong, ritual and song lyrics. 2) 2) Reflection of the 2nd principle value is found in the semiotics of gender equations in gamelan music instruments, Gamelan player's way of playing, how to treat gamelan and in song lyrics. 3) values 3rd precepts contained in the system tone counterpoint, Gamelan and togetherness among the players in the lyrics. 4) Reflection of the fourth precept is in the semitics of the leader in the gamelan music instrument. 5) Reflection of the 5th grade values is contained in all Gamelan music instruments, song lyrics and flavors created after watching Sundanese gamelan performances. Keywords: Reflective, Value, Pancasila, Art, Gamelan, Sundanese, Salendro barrel.